Discover answers to your most pressing questions at Westonci.ca, the ultimate Q&A platform that connects you with expert solutions. Join our Q&A platform to get precise answers from experts in diverse fields and enhance your understanding. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
a3=25
a8=-10
first, a3=25 will be 25= a + (3-1)×d that is the formula of the Arithimetic function genrally→ an=a (which is the first term..that we wanted in this case) + n-1 (n is the order of wanted term..we already has the term which is 3) × d (the common ration).
So, 25=a+(3-1)×d
25=a+2d
25-2d=a rearrange
a= 25-2d
We will take this equation and subsitute it in the other equation which is -10=a+ (8-1)×d
so it will be -10=25-2d+(8-1)×d
-10= 25-2d+7d sum the d
-10= 25+5d
-10-25= 5d
-35=5d
-35/5=d
-7= d
Now that we have the d we can go back to the equation of a= 25-2d and know the value of a
a= 25-2×-7
a1=39
d=-7
We appreciate your time on our site. Don't hesitate to return whenever you have more questions or need further clarification. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.